Keragaan Hibrida Hasil Persilangan Cabai Besar X Cabai Keriting di Lahan Gambut - Haice, Rika Neli; Tabrani, Gunawan; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The experiment was conducted on January 28 to june 30, 2013 in Peatland Experimental garden, Agriculture Faculty, University of Riau, Rimbo Panjang Village, Tambang district Kampar regency. The experimental design used was randomized block design consisting of 8 treatment in the 3 groups at different soil conditions that required 24 units of the experiment. Data were statistically analyzed using analysis of variance, followed by Duncan’s test New Multiple Range Test (DNMRT) at the level of 5%. Variables measured were the age flower appearance, age of harvest, plant height, dichotomous height, stem diameter, canopy width, fruit length, fruit diameter, weight per fruit and fruit weight per plant. The results showed that genotypes tested had adaptability and yield are quite good in peatland and different between genotypes. Genotype C-5 x C-120, C-5 x C-159 and TM 999 has a plant height, larger stem diameter, day to flowering and harvesting are faster. Dichotomous high owned by genotype C-5 x C-159, C-19x C-120 and TM 999, while the long pieces owned by genotype C-5 x C-159 and C-19 x C-120 and weight per fruit and weight highest fruit per plant owned by genotype C-5 x C-120. Keyword : Capsicum annum, peatland and yield